2009
DOI: 10.1080/17429140802710658
|View full text |Cite
|
Sign up to set email alerts
|

Do adult leaf beetles (Plagiodera versicolora) discriminate between odors from intact and leaf-beetle-infested willow shoots?

Abstract: We investigated how adults of willow leaf beetle Plagiodera versicolora find shoots with new leaves that were suitable food resources for them by focusing on shoot odor. Female and male beetles (starved and satiated) preferred the odor from intact shoots of Salix eriocarpa to clean air. Starved females preferred odor from shoots with leaves infested by conspecifics to odor from intact shoots. However, satiated females as well as starved and satiated males showed no significant discrimination between the two od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…We recently reported that ladybird (Aiolocaria hexaspilota) adults showed no preference for S. eriocarpa infested by leaf beetle adults (non-prey) over uninfested plants, but moved more often to the willow plants infested by leaf beetle larvae (prey) than to uninfested plants (Yoneya et al 2009b). Furthermore, adult P. versicolora (either satiated or starved) are attracted to uninfested S. eriocarpa leaf volatiles, while only starved female P. versicolora are attracted to adult-infested S. eriocarpa volatiles in their foraging (Yoneya et al 2009a). Here, P. versicolora larvae-induced volatiles are shown to affect the behavior of conspecific larvae as well.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We recently reported that ladybird (Aiolocaria hexaspilota) adults showed no preference for S. eriocarpa infested by leaf beetle adults (non-prey) over uninfested plants, but moved more often to the willow plants infested by leaf beetle larvae (prey) than to uninfested plants (Yoneya et al 2009b). Furthermore, adult P. versicolora (either satiated or starved) are attracted to uninfested S. eriocarpa leaf volatiles, while only starved female P. versicolora are attracted to adult-infested S. eriocarpa volatiles in their foraging (Yoneya et al 2009a). Here, P. versicolora larvae-induced volatiles are shown to affect the behavior of conspecific larvae as well.…”
Section: Discussionmentioning
confidence: 98%
“…Studies on the response of herbivorous arthropods to plant volatiles have focused mainly on adult herbivores finding a host plant for their oviposition. Uninfested leaves emit a blend of volatiles that can be exploited by adult herbivores as information indicating the presence of a host plant (e.g., Bernays and Chapman 1994;Dicke and van Loon 2000;Yoneya et al 2009a). Foraging adult herbivores also use volatiles from infested plants for host search; some of these odors act as attractants (Bolter et al 1997;Dicke and van Loon 2000;Kalberer et al 2001;Horiuchi et al 2003) and some as repellents (Dicke 1986;Dicke and van Loon 2000;De Moraes et al 2001;Kessler and Baldwin 2001;Horiuchi et al 2003;Heil 2004;Yoneya et al 2009a), thus preventing colonization of food resources that are infested by the same or different herbivore species.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, other willow species that share a niche with S. eriocarpa in the wild could also attract A. hexaspilota when infested by P. versicolora, although volatile profiles could be species specific. Plagiodera versicolora males and females (satiated and starved) are reported to prefer intact shoot leaf odour to clean air, and only starved females prefer odour from infested shoots to odour from intact shoots (Yoneya et al ., 2009). Thus, tritrophic interactions mediated by plant volatiles in natural willow communities could be more complicated than expected.…”
Section: Discussionmentioning
confidence: 99%
“…Overwintered, reproductively active females are active for about six weeks in the field (Kher et al 2011) and have to find suitable hosts for their progeny whereas males at this time are relatively short-lived (Haynes and Gage 1981). Gender can contribute to differential responses to olfactory cues associated with plant volatiles (Yoneya et al 2009). Adults of willow leaf beetle, Plagiodera versicolora (Laicharting) (Coleoptera: Chrysomelidae), locate their host using odours from newly formed shoots of Salix eriocarpa; females respond to the cues from intact shoots and those infested by conspecifics in greater proportions than males (Yoneya et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Gender can contribute to differential responses to olfactory cues associated with plant volatiles (Yoneya et al 2009). Adults of willow leaf beetle, Plagiodera versicolora (Laicharting) (Coleoptera: Chrysomelidae), locate their host using odours from newly formed shoots of Salix eriocarpa; females respond to the cues from intact shoots and those infested by conspecifics in greater proportions than males (Yoneya et al 2009). Similarly, female Colorado potato beetle, Leptinotarsa decimlineata L. (Coleoptera: Chrysomelidae), are more responsive to volatile cues associated with their host compared to males (Landolt et al 1999).…”
Section: Discussionmentioning
confidence: 99%